Interference of coarse and fine particles of different shape in mixed porous beds and filter cakes - Mota, M. (2003)
In solid–liquid separation the knowledge of solids packing structure is important to control permeability and dewaterability. In particular, cakes formed in filtration are often represented by the composition in coarse and fine particles. In this work cakes were modelled by mixing a bed of coarse (spheres) and fine (kieselguhr of three types and kieselgel) particles with a wide size distribution, in order to obtain beds with different proportions of plate and rod-like particles. Size ratio of glass beads to kieselguhr particles were in the range 23–30. Porosity and permeability were measured for a range of large particle fraction in the mixture from 0 up to 1.0. The fractional porosity of each particle fraction was introduced as a parameter. The approach proposed in this work was also successfully applied to different published filtration data. It was found that (1) the presence of more than 10% of fines in the coarse granular bed significantly reduces the cake permeability; (2) to improve cake permeability the volume fraction of filter aid in suspension must be at least 50–60% of total solid volume; (3) obtained data may be used to control the porosity of a mixture, if the fractional porosity of large and small particles is known or to estimate mixture tortuosity.